(untitled) (International Journal of Engineering and Computer Science, 2015)
Glucometer is device used by diabetics to measure blood glucose levels. Blood glucose testing is an important part of controlling blood glucose. One important goal of diabetes treatment is to keep the blood glucose levels near the normal range of 70 to 120 mg/dl before meals and under 140 mg/dl one to two hours after meal. Smart diabater is bluetooth enable hardware and it sends glucometer data to mobile application for data management and analysis. This can help to make an effective diabetes management program. Smart phone application shows data in graphical format. Each test result plotted along the time axis according to the time when the test is performed. Also it shows normal glucose level. On the basis of lunch and dinner time it distinguish glucose readings, it calculate average of pre-prandial reading and post- prandial reading average and glucose profile. According to difference between changes in glucose levels it suggests food list.